2021
DOI: 10.2147/bctt.s339607
|View full text |Cite
|
Sign up to set email alerts
|

Based on BATMAN-TCM to Explore the Molecular Mechanism of Xihuang Pill Regulating Immune Function to Treat Breast Precancerous Lesions

Abstract: Objective:The specific mechanism of Xihuang Pill in the treatment of breast precancerous lesions and breast cancer has not yet been elucidated. Methods: In our study, BATMAN-TCM (a Bioinformatics Analysis Tool for Molecular mechanisms of Traditional Chinese Medicine) was used to forecast the relationship among chemical components, immune targets, and diseases of each herb in Xihuang Pill and constructed a component-target-disease network. Taking breast precancerous lesion model rats as the research object, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In recent years, XHP as a natural product draws increasing attention in the prevention and treatment of BrCa [8][9][10][11][17][18]. However, the relationship between XHP and ferroptotic for BrCa has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, XHP as a natural product draws increasing attention in the prevention and treatment of BrCa [8][9][10][11][17][18]. However, the relationship between XHP and ferroptotic for BrCa has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The association of ferroptosis and tumor-immune cell in ltration and immunotherapy are closely related in BrCa according to the reported literature [19]. XHP has been reported to modulate the IL-2 and IFN-γ levels and the content of B7-1 cells, Treg cells, CD3 + T cells, and CD8 + T cells, increase the function of the mononuclear phagocytic cells, and to further enhance immune function and play an antitumor effect [10,17,20]. So, whether XHP is involved in the regulation of immune responses by eigh ferroptosis genes related to the BrCa patient's prognosis still has to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Yang Shen et al found that most tumour-in ltrating CD8 + CD103 + tissue-resident memory T cells in gastric cancer tissue were TEM cells compared with nontumor tissue which were relational with the prognosis of patients suffered from gastric cancer [33]. Li Dehui et al found that Xihuang Pill could regulate Th1 and Th2 cell levels in rats with precancerous lesions, thereby regulating the Th1/Th2 ratio [34]. A study demonstrated that the expanded M1-like macrophage signature was enriched in BLCA samples and was associated with reduced OS in BLCA patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical components of Sishen Decoction were searched and obtained based on the Batman-TCM database and screened and supplemented with literature ( 14 ). The simplified molecular input line entry system (SMILES) notations and 2D structures of the chemical components were determined by searching the names of the obtained chemical components in the PubChem database ( https://pubchem.ncbi.nlm.nih.gov ).…”
Section: Methodsmentioning
confidence: 99%